Attention to inattention: Effect of the other's attentional state on visual search performance in chimpanzees. (April 2023) - Tomonaga, Masaki; Imura, Tomoko
In the present study, we examined the effects of the other's triadic attention to objects on visual search performances in chimpanzees. We found the search-asymmetry-like effect of the other's attentional state; the chimpanzees searched a target object not attended by the other individual more efficiently than that attended (Experiment 1). Additional experiments explored the possibility that the other individual "holding an object but not looking at it" led to expectancy violation (Experiment 2) or the role of nonsocial cues such as the proximity relation between the head and the object (Experiment 3). Still, these accounts alone did not explain this effect. It was also shown that the other's attentional state affected the chimpanzees' performances more readily as the interference effect than the facilitation effect (Experiment 4). Furthermore, the same effect was observed in the visual search for the gaze (head direction) of others (Experiment 5). We obtained the same results using photographs of chimpanzees (Experiment 6). Contrary to the chimpanzees, humans detected the object to which attention was directed more efficiently than vice versa (Experiment 7). The present results may reflect species differences between chimpanzees and humans in processing triadic social attention.